Application of phase change material heat storage device for control of Varroa mites in beehives - Tapia Brito, Emmanuel (2022)
Bees are commonly thought to be useful for generating honey. In the natural environment, pollination of flowers, on the other hand, has the greatest ecological impact on bees. Both the importance of bees to humans and the urgent need to take action to prevent their unjustifiable and slow elimination are generally understood. Bees are now subjected to a variety of stresses and problems. They had to face with the natural challenges in their environment, such as temperature, humidity and predators etc. The major goals of this project are to employ sustainable energy technologies to eliminate the most serious threat to bees, Varroa mites, to design a practical prototype that is easy enough for beekeepers to use, and to show that heat treatment is a non-harmful technique for bees and their products.